Atomic and molecular spectra emitted by normal liquid ⁴He excited by corona discharge - Li, Z.-L.; Bonifaci, N.; Denat, A.; Atrazhev, V.M.; Shakhatov, V.A.; von Haeften, K. (Физика низких температур, 2011)
The liquid ⁴He at fixed temperature 4.2 K and different pressures up to 8 MPa was excited by corona discharge of both negative and positive polarity. Emission of He I atomic lines and He₂ molecular bands are observed. In negative corona the lines spectra show a distinct blue-shift and line-broadening, which becomes stronger with the pressure increasing. The rotational structure of molecular bands is resolved at pressures (0.1–0.2) MPa. The blue shift of the Q-branch maximum at different pressures was observed. Rotational temperature of 900 K has been estimated for the d³Σ⁺u-b³Πg molecular band. A positive corona was realized on a point anode for fewer radii of the electrode and larger voltage than in the negative corona. Electric currents in both negative and positive corona differ weakly. Spectral analysis of the radiation from the positive corona shows qualitative differences of spectral features of these discharges. The spectra observed in the positive corona have marked nonsymmetric shape. The asymmetric atomic and molecular spectra show an increased intensity of their long-length (red) wings.